Determining the effects of duct fittings on volumetric air flow measurements - Hickman, Craig (Kansas State University, 2010)
The purpose of the research was to quantify the influence of several duct disturbances on volumetric flow rate measurements and use these in developing guidelines for field technicians. This will assist the field technicians in making more accurate volumetric air flow measurements in rectangular ducts during a test and balance operation. Multiple duct sizes, fittings, probes, traverse algorithms, and locations upstream and downstream of the disturbances are used to compare a variety of situations. The two traverse algorithms used are the log-Tchebycheff and equal area methods. Two upstream and five downstream locations are tested for each duct configuration. Two air velocity probes are used for local velocity measurements on each traverse: a pitot-static probe and a hot wire anemometer. A nozzle bank and Air Flow Measurement Station are used as the flow measurement standards for comparison with each traverse. This paper discusses the setup and initial results of ASHRAE 1245-RP. Data collected subsequent to this thesis will complete the balance of results and will be collected and analyzed by other researchers. Results will be summarized and presented in a way which allows technicians to use it in the field for more accurate balancing results.
Keywords: HVAC; ASHRAE; Duct; Air flow; Engineering, Mechanical (0548)